Managing Land‐based CDR: BECCS, Forests and Carbon Sequestration. (6th September 2020) - Brack, Duncan; King, Richard
Abstract: Decisions about when, where and how to achieve widespread carbon dioxide removal (CDR) are urgently required. Delays in developing the requisite policy and regulatory frameworks increase the risks of overshooting climate goals and will necessitate much larger negative emissions initiatives in the future. Yet the deployment of bioenergy with carbon capture and storage (BECCS) at the scales assumed under most Paris‐Agreement‐compliant emission‐reduction pathways is unlikely. More generally, the sustainability of large‐scale BECCS is questionable given its extensive land, water, and energy requirements for feedstocks and the competing necessity of these resources for the provision of ecosystem services and attainment of multiple Sustainable Development Goals. BECCS on a more limited scale, however, could have more benign impacts if feedstocks were restricted to wastes and residues. There is also widespread recognition that extensive afforestation, reforestation and forest restoration have critical roles in reducing greenhouse gas emissions to net zero. To date there has been little focus on the optimum strategies for integrating land‐based CDR approaches – under which circumstances forest areas are best left undisturbed, managed for conservation, and/or managed for harvested wood products, and how these options affect the availability of residual feedstocks for BECCS. This paper reviews this debate and suggests appropriate policy measures. Abstract : No single NET, whether BECCS, nature‐based, or otherwise, will achieve the scale of CDR required in the vast majority of 1.5°C and 2°C mitigation scenarios, let alone do so sustainably. But portfolios of multiple NETs, deployed sensitively at modest scales, will be invaluable for achieving climate security.